Fatty Acid-Binding Protein 5 Modulates Brain Endocannabinoid Tone and Retrograde Signaling in the Striatum - Fauzan, Mohammad; Oubraim, Saida; Yu, Mei; Glaser, Sherrye T.; Kaczocha, Martin; Haj-Dahmane, Samir (Frontiers in Cellular Neuroscience, 2022)
The endocannabinoids (eCBs) anandamide (AEA) and 2-arachidonoylglycerol (2-AG) are endogenous lipid neurotransmitters that regulate an array of physiological functions including pain, stress homeostasis, and reward. Fatty acid binding protein 5 (FABP5) is a key modulator of intracellular eCB transport and inactivation. Recent evidence suggests that FABP5 controls synaptic 2-AG signaling at excitatory synapses in the dorsal raphe nucleus. However, it is currently not known whether this function extends to other brain areas. To address this, we first profiled eCB levels across several brain areas in FABP5 knockout mice and wild-type controls and report that FABP5 deletion elevates AEA levels in the striatum, prefrontal cortex, midbrain, and thalamus, as well as midbrain 2-AG levels. The expression of eCB biosynthetic and catabolic enzymes was largely unaltered in these regions, although minor sex and region-specific changes in the expression of 2-AG catabolic enzymes were observed in female FABP5 KO mice. Robust FABP5 expression was observed in the striatum, a region where both AEA and 2-AG control synaptic transmission. Deletion of FABP5 impaired tonic 2-AG and AEA signaling at striatal GABA synapses of medium spiny neurons and blunted phasic 2-AG mediated short-term synaptic plasticity without altering CB1R expression or function. Collectively, these results support the role of FABP5 as a key regulator of eCB signaling at excitatory and inhibitory synapses in the brain.